Acquiring Basic Chemistry Concepts through Virtual learning in Nigerian Senior Secondary Schools - Michael Olubunmi Odewumi; Ayotunde Atanda Falade; Adewale Olusegun Adeniran; David Akinjide Akintola; Grace O. Oputa; Sunday Abiodun Ogunlowo (Universitas Muhammadiyah Surakarta, 2020)
Virtual learning has emerged as an ideal platform for learning. Different e-learning packages has been developed to solve instructional problems globally, but in Nigeria few instructors are aware of the usage of this technologies. Therefore, the study examined the acquisition of basic chemistry practical through virtual among Senior Secondary School students in Ado Ekiti, Ekiti State. Nigeria. The study further considered gender and achievement level of the students taught with virtual learning.A survey designed method was adopted, sample constituted of 28 Senior Secondary School II Chemistry students, of which fourteen (14) were male and fourteen (14) also female. The results reveal that virtual learning enhances students’ understanding of laboratory chemistry concepts, acquisition and improve performances in chemistry as an alternative to actual chemistry laboratory in Nigerian Senior Secondary Schools.